PERANGKAT LUNAK KONVERSI DIAGRAM ALIR MENJADI KODE PROGRAM PASCAL - Sukarsa, I Made; Care Khrisne, Duman (Majalah Ilmiah Teknologi Elektro, 2012)
The most important thing in making a program is to design algorithms. One of the design algorithm is a flowchart depiction of the most frequently used. Flowchart is visualization of run the command that states the program's operation, then the appropriate flow chart will be able to produce the program. Guided by mastering the basics of algorithms and syntax equivalent in Pascal and modeling of the database is expected to develop applications for the conversion of flowcharts into Pascal program code. The results of this study is expected to assist in facilitating student learning Pascal programming language